2015
DOI: 10.1016/j.envint.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sources and human exposure implications of concentrations of organophosphate flame retardants in dust from UK cars, classrooms, living rooms, and offices

Abstract: Concentrations of a number of organophosphate flame retardants (PFRs) were measured in floor dust collected from UK living rooms (n = 32), cars (n = 21), school and child daycare centre classrooms (n = 28), and offices (n = 61). While concentrations were overall broadly within the range of those reported previously for North America, Japan, and other European countries, median concentrations of TCIPP in all UK microenvironments exceeded those reported elsewhere in the world. Moreover, concentrations of TCIPP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
74
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 32 publications
(42 reference statements)
15
74
3
Order By: Relevance
“…However, TCPP was detected in indoor air (S1, TCPP = 10.25 ng/m 3 ) collected in classroom without PUF foam furniture. This is in accordance with results from Brommer and Harrad (2015), who also found TCPP in dust samples collected from rooms without PUF foam furniture. Thus, PUF furniture and PUF insulation foam cannot be the only source for TCPP in indoor microenvironments.…”
Section: Principal Component Analysissupporting
confidence: 94%
See 2 more Smart Citations
“…However, TCPP was detected in indoor air (S1, TCPP = 10.25 ng/m 3 ) collected in classroom without PUF foam furniture. This is in accordance with results from Brommer and Harrad (2015), who also found TCPP in dust samples collected from rooms without PUF foam furniture. Thus, PUF furniture and PUF insulation foam cannot be the only source for TCPP in indoor microenvironments.…”
Section: Principal Component Analysissupporting
confidence: 94%
“…In addition, other studies reported much higher concentrations of OPFRs in dust collected in private cars than in private homes and offices in Germany (Brommer et al 2012), UK (Brommer and Harrad 2015), Kuwait, Pakistan (Ali et al 2013), and Egypt (Abdallah and Covaci 2014). On average, a personal vehicle contains over 105 kg of plastics (9.3 % of materials used), and this proportion continues to increase with time (EFRA 2015).…”
Section: Concentrations Of Opfrs In Indoor Air Of Different Microenvimentioning
confidence: 93%
See 1 more Smart Citation
“…While our UK study found no significant relationships between PFR concentrations in dust from cars, classrooms, homes, and offices and the presence of putative PFR sources in such UK microenvironments [11]; the same study did highlight elevated concentrations of TCIPP in house dust and suggested that this was likely attributable to extensive use of TCIPP in couch foam, as reported in the US [28]. This study explores this further, by comparing concentrations of TCIPP in Australian couch dust and from living rooms in which the couch was located; hypothesising that significantly elevated concentrations of TCIPP in couch compared to floor dust, combined with significant positive correlation between the two groups, would indicate couches to be a significant source.…”
Section: Introductionmentioning
confidence: 62%
“…We reported recently on concentrations of PFRs in samples of floor dust from UK cars, school classrooms, homes, and offices [11].…”
Section: Introductionmentioning
confidence: 99%